PROBLEMATIKA PERKAWINAN USIA DINI MASYARAKAT KABUPATEN SIDRAP - Anwar, Wirani Aisiyah; Jumiyati, Jumiyati; Hakim, Abd.; Wahyu, A. Rio Makkulau (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2025)
This study identifies the issue of early marriage in Sidrap Regency by exploring the factors influencing the tendency for marriage at a young age. Using qualitative research methods such as in-depth interviews and participatory observation, the author analyzes the social, economic, and cultural impacts that drive early marriage. The findings reveal that social pressure from the community, gender inequality, and limited access to education are the main factors influencing the decision to marry at an early age. Declining education levels, traditional views, and social norms that regard early marriage as a solution to economic problems further exacerbate the situation. This research provides important insights for the government and stakeholders in designing more effective policies to prevent early marriage. The findings are also expected to contribute to a deeper understanding of the challenges faced by the Sidrap community, as well as guide efforts to protect the rights of children and adolescents from early marriage.